Empirical Studies Assessing the Perceptions and Knowledge of Medicine in Mongolia: A Nationwide Population-Based Study - Dulmaa Lkhagvasuren; Uranbileg Bayarbat; Ganbat Khongorzul; Purevjav Tsetsgee; Muhammad Shahzad Aslam (Indonesian Journal of Pharmacy, 2024)
The availability and affordability of medicine is an essential issue in any population globally, and drug regulatory agencies need the information to prevent an unforeseen matter and take necessary decisions by relevant agencies so that medicine will be available at an affordable price. Moreover, it is also essential to assess the consumer perception of patterns and knowledge about medicine use, subject to perception bias and belief bias. The current study examines consumers’ perceptions of medicine availability, medicine spending, affordability of medicine, patterns and knowledge of medication use. A nationwide cross-sectional study was performed in Mongolia. The survey consists of nineteen closed-ended questionnaire items. The manuscript has presented according to The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines on the cross-sectional study. A total of seven thousand five hundred and thirty-two (n=7532) had participated in the study. 46.3% of the study population consider the quality during buying of medicine. The average spending of medicine per month in Mongolia is 4.00 USD-17.00 USD/= per month. A large percentage of the population (47.8%) has skipped buying prescription drugs due to affordability issues. 47.4% of the population believe that the price of the drug sold in the market is expensive. A surprisingly 56% of study population indicate that the pharmacy does not have enough type and stock of drug. The study population (40.4%) does not have enough awareness about falsified medicine, and 30.4% cannot buy discounted medicine covered by the health insurance fund. A considerable percentage of the population (74.2%) take medicine according to doctor instructions and is firmly in favour of the government to regulate the drug prices (79.9%). The current study showed consumers’ perception, pattern, knowledge and affordability about medicines. The results indicate a lack of education by the healthcare providers on falsified medicine, the financial burden of medicine on the population, and the unavailability of different medicine stock.